Entrepreneurship and self-help among Black Americans : a reconsideration of race and economics - Butler, John S. (John Sibley) (Albany : State University of New York Press, 2005)
"Since its publication in 1991, Entrepreneurship and Self-Help among Black Americans has become a classic work, influencing the study of entrepreneurship and, more importantly, revitalizing a research tradition that places new ventures at the very center of success for black Americans. This revised edition updates and enhances the work by bringing it into the twenty-first-century. John Sibley Butler traces the development of black enterprises and other community organizations among black Americans from before the Civil War to the present. He compares these efforts to other strong traditions of self-help among groups such as Japanese Americans, Jewish Americans, Greek Americans, and exciting new research on the Amish and the Pakistani. He also explores how higher education is already a valued tradition among black self-help groups - such that today their offspring are more likely to be third and fourth generation college graduates. Butler challenges the myth that nothing can be done to salvage America's underclass without a massive infusion of public dollars, and offers a fresh perspective on those community based organizations and individuals who act to solve local social and economic problems."--Jacket
Machine generated contents note: 1. sociology of entrepreneurship -- 2. Race and entrepreneurship : a respecification -- 3. "To seek for ourselves" : benevolent, insurance, and banking institutions -- 4. Entrepreneurship under an economic detour -- 5. Durham, North Carolina : an economic enclave -- 6. Tulsa, Oklahoma : business success and tragedy -- 7. reconstruction of race, ethnicity, and economics : toward a theory of the Afro-American middleman -- 8. present status of Afro-American business : the resurrection of past solutions.
Includes bibliographical references (pages 381-397) and index.
Print version record.
JSTOR
Keywords: African Americans -- Economic conditions; African American businesspeople; Entrepreneurship -- United States; Noirs américains -- Conditions économiques.; Gens d'affaires noirs américains.; Entrepreneuriat -- États-Unis.; BUSINESS & ECONOMICS -- Entrepreneurship; African American businesspeople; African Americans -- Economic conditions; Entrepreneurship; United States; Wirtschaftliche Lage; Mittelständischer Unternehmer; USA; Schwärze